Pengaruh Marketing Mix Terhadap Keputusan Menabung Nasabah Bank Syariah Indonesia di Kota Bengkulu - Shar, Aan; Fitri, Marsellina (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2024)
The aim of this research is to determine the influence of Marketing Mix on the Savings Decision-Making of customers of Indonesian Sharia Banks in the city of Bengkulu. This study employs a descriptive research approach with primary data collection methods and the sampling technique used is incidental sampling with a total of 100 respondents. The data analysis techniques utilized include validity testing, reliability testing, and multiple linear regression. The research findings indicate that Product, Price, Place, and Promotion, both partially and simultaneously, have a significant impact on the Savings Decision-Making of customers of Indonesian Sharia Banks in the city of Bengkulu.